The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Keywords: BAUMAN, Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

The Political Economy of Mesoamerican States: An Economic Ethnographer's View - Halperin, Rhoda (The Political Economy of Ancient Mesoamerica: Transformations During the Formative and Classic Periods, 2007)
KM: outlines a generic model of political economy based on Polanyi's writings and explores some of its implications.
Keywords: Mesoamerica; economic anthropology

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state